PENGEMBANGAN MEDIA POWERPOINT DIGITAL BERBASIS PBL DALAM PEMBELAJARAN IPAS KELAS VDI SEKOLAH DASAR - Weni Anggraini; Yeni Erita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the suboptimal use of digital media in producingvaried and engaging learning materials for elementary school learning. The aim ofthe study was to develop a digital PowerPoint medium based on Problem-BasedLearning (PBL) utilizing the action feature for Grade V Science, Environment, andSocial Studies (IPAS) learning that is valid, practical, and effective. The methodused was research and development (R&D) with the ADDIE model, which includesthe stages of analysis, design, development, implementation, and evaluation. Datacollected consisted of qualitative data from interviews, observations, and expertvalidation, as well as quantitative data from validation results, teacher and studentresponse questionnaires, and effectiveness tests. The trials were conducted atSDN 11 Indarung, with research subjects from SD Semen Padang and SDN 20Indarung. Validation results for content, language, and media increased from75.22% in the first validation to 94.87% in the second validation (highly valid).Practicality reached 96.42% (teachers) and 98.80% (students) in the trial school,and 94.63% (teachers) and 93.21% (students) in the research schools.Effectiveness, based on the N-Gain test, showed results of 78.04% in the trialschool and 77.77%–79.08% in the research schools. Therefore, the PBL-basedPowerPoint medium was declared valid, practical, and effective for use in Grade VIPAS learning.